The effect of guided imagery on stress and attachment of mothers of premature infants in neonatal intensive care unit: A quasi-experimental study - Farnaz Safari; Lida Nikfarid; Maliheh Nasiri; Maryam Mahdizadeh Shahri; Nahid Naseri; Azam Shirin abadi farahani; Maryam Varzeshnejad (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2022)
Background. Premature birth, in addition to causing health problems in infants, increases stress in the mother and reduces attachment between mother and baby. Therefore, the present study was conducted to determine the effect of guided visualization on stress and attachment of mothers of preterm infants in the neonatal intensive care unit (NICU). Methods. This quasi-experimental study was performed on 35 mothers with premature infants admitted to the NICU of Mahdieh Hospital of Shahid Beheshti University of Medical Sciences, Tehran, Iran. Mothers were selected by available sampling method and randomly assigned into intervention and control groups. For mothers in the intervention group, the intervention was performed from the first to the fifth day of birth through training and sending guided imagery files. On the day of admission and discharge, the parental stress questionnaire and the postpartum attachment questionnaire were completed by the mother. SPSS software (version 20) was used to analyze the data. Results. The mean total score of maternal attachment on the fifth day of the intervention was significantly higher in the intervention group (P<0.001). Also, the mean total score of mothers' attachment status on the day of discharge was significantly higher in the intervention group (P<0.001). Conclusion. Implementation of guided visualization program reduced stress in mothers with premature infants admitted to the NICU, and consequently increased the level of attachment. Practical Implications. Mothers are the primary caregivers of infants, and promoting maternal health has an effect on infants. In addition to reducing stress in preterm infants, this study can help improve the quality of infant care and increase attachment and parenting. The present study offers a completely cost-effective way to reduce the costs of long-term hospitalization and improve the quality of nursing.